Instant Chef starter : a practical guide to getting started with Chef, an indispensable tool for provisioning and managing your system's infrastructure /: a practical guide to getting started with Chef, an indispensable tool for provisioning and managing your system's infrastructure. (2013) - Unknown
No abstract available